2008
DOI: 10.1007/s10530-008-9220-7
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkinseed sunfish (Lepomis gibbosus) invasions facilitated by introductions and nature management strongly reduce macroinvertebrate abundance in isolated water bodies

Abstract: The pumpkinseed sunfish, Lepomis gibbosus, originates from Eastern North America and was introduced to the Netherlands in 1902 as an aquarium and garden pond fish. At present the pumpkinseed is widely spread throughout the Netherlands and occurs in a variety of aquatic habitats. It is especially abundant in moorland pools, fishing ponds and urban waters. Strong population development of the pumpkinseed appears to be facilitated by nature management practices in existing ponds (the removal of accumulated organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 24 publications
1
42
0
1
Order By: Relevance
“…However, the increased attention to northwestern populations has revealed pumpkinseed to be more widely distributed within countries of northwestern Europe than was previously believed (e.g. Verreycken et al 2007;Van Kleef et al 2008), despite the fact that the pumpkinseed is considered a warmwater species. The study of northwestern European populations is especially relevant for understanding how pumpkinseed lifehistory varies according to local climate across a latitudinal cline, resulting in a different invasive potential.…”
Section: Introductionmentioning
confidence: 94%
“…However, the increased attention to northwestern populations has revealed pumpkinseed to be more widely distributed within countries of northwestern Europe than was previously believed (e.g. Verreycken et al 2007;Van Kleef et al 2008), despite the fact that the pumpkinseed is considered a warmwater species. The study of northwestern European populations is especially relevant for understanding how pumpkinseed lifehistory varies according to local climate across a latitudinal cline, resulting in a different invasive potential.…”
Section: Introductionmentioning
confidence: 94%
“…Although several fish species occurring in the Rhine have been identified as feeding on gammarideans (Kelleher et al 1998 they could not be held in our aquaria for several reasons. Therefore, in this study, the pumpkinseed sunfish (Lepomis gibbosus) was used as the top predator because of its small size, its predatory behaviour with respect to macroinvertebrates including gamnmarideans (Van Kleef et al 2008) and because this fish could be easily obtained from the aquarium shop. It is not occurring in the Rhine but functions in our experiments as a representative of any predatory fish.…”
Section: Aquarium Experimentsmentioning
confidence: 99%
“…It is considered that habitat alteration by humans may be responsible for the establishment of some invasive fish species in Mediterranean-type streams and the increase in species invasiveness , Almeida et al 2009). Van Kleef et al (2008) found that pumpkinseed is more abundant in fishing and moorland ponds, urban waters, and also water basins from which organic sediments, macrophytes, or inert materials have been obtained. Analysis of the relation between water body management and pumpkinseed abundance confirms the role of humans in the growth of pumpkinseed populations.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that in most of the European ecosystems where pumpkinseeds have been introduced they influenced directly or indirectly native species through competition for food and predation on fish eggs and endemic molluscs (García-Berthou and MorenoAmich 2000, Copp et al 2005b), zooplankton (Brabrand and Saltveit 1989), and as well as macroinvertebrates (van Kleef et al 2008, Nikolova et al 2009). …”
mentioning
confidence: 99%
See 1 more Smart Citation